Isolation, Characterization, and Genome Engineering of a Lytic Pseudomonas aeruginosa Phage - Xiaomei Cong; Shuang Zhao; Qing Zhang; Shuo Liu; Youming Zhang; Fu Yan (Microorganisms)
Antibiotic-resistant bacterial infections have become one of the leading causes of human mortality. Bacteriophages presented great potential for combating antibiotic-resistant infections in the post-antibiotic era due to their high host specificity and safety profile. Pseudomonas aeruginosa, an opportunistic pathogenic bacterium, has shown a surge in multidrug-resistant strains, severely impacting both human health and livestock. In this study, we successfully isolated and purified a P. aeruginosa-specific phage, PpY1, from feces collected from a breeding farm. This phage harbors a short tail and a 43,787 bp linear genome, and exhibited potent lytic activity against several pathogenic P. aeruginosa strains. Leveraging Transformation-associated recombination (TAR) cloning and phage assembly techniques in a P. aeruginosa host lacking a restriction–modification system, we developed a genome engineering platform for PpY1. Through a systematic gene knockout approach, we identified and eliminated 21 nonessential genes from the PpY1 genome, resulting in a series of phages with reduced genomes. This research not only enhances our understanding of the phage genome but also paves the way for the functional optimization of phages, e.g., broadening the host spectrum and elevating the lytic capacity, dedicated towards the treatment of bacterial infections.